2017
DOI: 10.1007/jhep06(2017)107
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutative duality and fermionic quasinormal modes of the BTZ black hole

Abstract: Abstract:We analyze the fermionic quasinormal modes of the BTZ black hole in the presence of space-time noncommutativity. Our analysis exploits a duality between a spinless and spinning BTZ black hole, the spin being proportional to the noncommutative deformation parameter. Using the AdS/CFT correspondence we show that the horizon temperatures in the dual CFT are modified due to noncommutative contributions. We demonstrate the equivalence between the quasinormal and non-quasinormal modes for the noncommutative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 80 publications
3
25
0
Order By: Relevance
“…Our results of QNM frequencies could reduce to the formula in Refs. [8,24,25] when the noncommutative parameters and the coupling constant disappear. We have found that the coupling constant ξ shifts the QNM frequencies but does not affect the structure of the area/entropy spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results of QNM frequencies could reduce to the formula in Refs. [8,24,25] when the noncommutative parameters and the coupling constant disappear. We have found that the coupling constant ξ shifts the QNM frequencies but does not affect the structure of the area/entropy spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…[8,25]. In this paper, we will devote to the QNM of the massless Dirac field in the noncommutative BTZ background.…”
Section: Fermionic Qnm In the Noncommutative Btz Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…B. NC scalar field in BTZ background and mapping to equivalent commutative model In view of the setting just described, in [54][55][56][57] a model was proposed that is based on the action…”
Section: A Noncommutative Frameworkmentioning
confidence: 99%
“…After using von-Neumann's method we find the criterion on BTZ parameters that lead to a quantum complete spacetime. In section III we first sketch the NC setting from our previous papers [22][23][24][25], and then proceed with the same analysis as in section II. We see that the range of BTZ parameters rendering the quantum completeness is enlarged.…”
Section: Introductionmentioning
confidence: 99%